Enjoyment of Physical Activity-Not MVPA during Physical Education-Predicts Future MVPA Participation and Sport Self-Concept - Jared D. Ramer; Natalie E. Houser; Robert J. Duncan; Eduardo E. Bustamante (MDPI AG, 2021)
There exists a general understanding that physical education (PE) is a means to create a physically healthy population. However, disagreements arise over primary practices within PE to achieve this end. The primary divergence is whether PE facilitators should primarily ensure participants exert a specific level of energy during class or develop their confidence, competence, knowledge, and motivation for meaningful physical activity (PA) participation outside of the PE classroom (referred to as physical literacy (PL)). This study uses structural equation modeling to examine associations between enjoyment of PA and minutes of moderate to vigorous physical activity (MVPA) in PE class in grade 5 (mean age = 10) and participation in PA and feelings about PA 1 year later, in grade 6 (mean age = 11), in the NICHD Study of Early Child Care and Youth Development (SECCYD, N = 1364). Enjoyment of PA in grade 5 predicted sport self-concept (β = 0.347, p ≤ 0.001), MVPA (β = 0.12, p ≤ 0.001), and enjoyment of PA (β = 0.538, p ≤ 0.001) in grade 6. These associations remained when including weekday MVPA performed in grade 5 as an indirect effect (β = 0.058, p ≤ 0.001). MVPA performed during PE in grade 5 was not associated with any PA outcomes in grade 6. Findings suggest PE instructors should prioritize PL development over maintenance of high energy expenditure during PE class for long-term MVPA.